2015
DOI: 10.3168/jds.2014-8386
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and crossbreeding parameters for production and fertility traits in Holstein, Montbéliarde, and Normande cows

Abstract: Breed differences and nonadditive genetic effects for milk production traits, somatic cell score (SCS), conception rate (CR), and days to first service (DFS) were estimated for Holstein × Montbéliarde and Holstein × Normande crossbreds, using an animal model adapted from the French genetic evaluation and extended to across-breed analysis. Inbreeding and breed differences were estimated from all purebred recorded cows. Only records from 1,137 herds with Holstein × Montbéliarde crossbred cows and from 1,033 herd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 27 publications
4
57
1
13
Order By: Relevance
“…Collection of FI and body trait observations of cows began 4 d postpartum and continued until 150 DIM. The objectives of this study did not include the investigation of lowly heritable traits such as fertility and survival because other studies with much larger sample sizes have compared CB and HO cows for those traits in commercial herds (Heins et al, 2012;Dezetter et al, 2015;Hazel et al, 2017a).…”
Section: Experimental Unitsmentioning
confidence: 99%
“…Collection of FI and body trait observations of cows began 4 d postpartum and continued until 150 DIM. The objectives of this study did not include the investigation of lowly heritable traits such as fertility and survival because other studies with much larger sample sizes have compared CB and HO cows for those traits in commercial herds (Heins et al, 2012;Dezetter et al, 2015;Hazel et al, 2017a).…”
Section: Experimental Unitsmentioning
confidence: 99%
“…For example, El‐Tarabany () found that HF × Brown Swiss (BS) hybrids were stronger, less susceptible to metabolic burden and more tolerant to changes in their daily ration compared to purebred HF. According to Dezetter and others (), the impact of heterosis is visible in improved efficiency, reproductive measures of cows and in the cytological quality of milk.…”
Section: Introductionmentioning
confidence: 99%
“…Although this phenomenon is widely acknowledged in animal and plant breeding789, the genetic basis of heterosis remains unclear. Three classical hypotheses, including dominance10111213, overdominance141516 and epistasis1718 have been proposed to explain heterosis.…”
mentioning
confidence: 99%